Alzheimer's disease research in the context of the national plan to address Alzheimer's disease. (June 2015) - Snyder, Heather M.; Hendrix, James; Bain, Lisa J.; Carrillo, Maria C.
Abstract: In 2012, the first National Plan to Address Alzheimer's Disease in the United States (U.S.) was released, a component of the National Alzheimer's Project Act legislation. Since that time, there have been incremental increases in U.S. federal funding for Alzheimer's disease and related dementia research, particularly in the areas of biomarker discovery, genetic link and related biological underpinnings, and prevention studies for Alzheimer's. A central theme in each of these areas has been the emphasis of cross-sector collaboration and private–public partnerships between government, non-profit organizations and for-profit organizations. This paper will highlight multiple private–public partnerships supporting the advancement of Alzheimer's research in the context of the National Plan to Address Alzheimer's.